Resistive Random Access Memories (RRAMs) Based on Metal Nanoparticles - Kiazadeh, Asal (2015)
It is demonstrated that planar structures based on silver nanoparticleshosted in a polymer matrix show reliable and reproducible switching properties attractive for non-volatile memory applications. These systems can be programmed between a low conductance (off-state) and high conductance (on-state) with an on/off ratio of 3 orders of magnitude, large retention times and good cycle endurance. The planar structure design offers a series of advantages discussed in this contribution, which make it an ideal tool to elucidate the resistive switching phenomena.